Archaeological expedition to al khashbah (2023): Rock art survey - Döpper, Stephanie (Athar: Bulletin of Archaeological Research in the Sultanate of Oman, 2025)
In 2023, a new project on rock art in Eastern Arabia, with special focus on the Al Sharqiyah North Governorate started. It aims at recording the spatial and chronological distribution of rock art as well as its integration into the natural and anthropogenic landscape. In the first field season from February to April 2023, over 4,000 rock art images have been recorded at the sites of Al Tasawir, Lizq, Al Khashbah and Al Rakhi. This encompassed digital sketches of the rock art panels, photography of the individual rock art images, taking of UTM coordinates, and vectorising the photographs on a computer later on. In addition, 3D models of all recorded sites were generated by structure-from-motion (SfM). As a citizen science component of the project, a smartphone application (Rock Art Oman) was developed that allows everyone to support the project by documenting rock art in an easy manner. This does not only provide more data for research but also help to foster the awareness of people in Oman for their rock art heritage.
Keywords: Archéologie -- Oman